'Click' chemistry synthesis and capillary electrophoresis study of 1, 4‐linked 1, 2, 3‐triazole AZT‐systemin conjugate. (28th May 2014) - Dobkowski, Michał; Szychowska, Aleksandra; Pieszko, Małgorzata; Miszka, Anna; Wojciechowska, Monika; Alenowicz, Magdalena; Ruczyński, Jarosław; Rekowski, Piotr; Celewicz, Lech; Barciszewski, Jan; Mucha, Piotr
<x xml:space="preserve">Abstract</x> The Cu(I) catalyzed Huisgen 1, 3‐dipolar azide‐alkyne cycloaddition (CuAAC) was applied for a nucleoside‐peptide bioconjugation. Systemin (Sys), an 18‐aa plant signaling peptide naturally produced in response to wounding or pathogen attack, was chemically synthesized as its N‐propynoic acid functionalized analog (Prp‐Sys) using the SPPS. Next, CuAAC was applied to conjugate Prp‐Sys with 3′‐azido‐2′, 3′‐dideoxythymidine (AZT), a model cargo molecule. 1, 4‐Linked 1, 2, 3‐triazole AZT‐Sys conjugate was designed to characterize the spreading properties and ability to translocate of cargo molecules of systemin. CuAAC allowed the synthesis of the conjugate in a chemoselective and regioselective manner, with high purity and yield. The presence of Cu(I) ions generated in situ drove the CuAAC reaction to completion within a few minutes without any by‐products. Under typical separation conditions of phosphate 'buffer' at low pH and uncoated fused bare‐silica capillary, an increasing peak intensity assigned to triazole‐linked AZT‐Sys conjugate was observed using capillary electrophoresis (CE) during CuAAC. CE analysis showed that systemin peptides are stable in tomato leaf extract for up to a few hours. CE‐ESI‐MS revealed that the native Sys and its conjugate with AZT are translocated through the tomato stem and can be directly detected in stem exudates. The results show potential application of systemin as a transporter of low molecular weight cargo molecules in tomato plant and of CE method to characterize a behavior of plant peptides and its analogs. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.